Pengaruh Ukuran Perusahaan, Umur Perusahaan, Profitabilitas, Solvabilitas dan Likuiditas terhadap Audit Report Lag - Sofi Dwiastuti Agustina; Jaeni Jaeni (Owner : Riset dan Jurnal Akuntansi, 2022)
This study seeks to examine the effect of company size, company age, profitability, solvency, and liquidity on audit report lag on tourism companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The number of samples in this study were 16 companies, selected with certain criteria using purposive sampling technique. The data analysis technique used in this research is panel data regression analysis using Eviews 9 software. The results showed that the firm age variable had a positive effect on audit report lag, while the profitability variable had a negative effect on audit report lag, while firm size, solvency and liquidity variables had no significant effect on audit report lag.